(untitled) (Journal of Universal Science Research, 2025)
Families raising children with disabilities face unique psychological and social challenges. This article explores the emotional dynamics within such families, highlighting the stressors experienced by parents, especially mothers, and the need for structured psychological support. Using data from Uzbek national sources and theoretical perspectives from scholars like M.N. Guskova, the article emphasizes the importance of social integration and inclusive policy support. The article also outlines the necessary institutional and psychological support mechanisms and explores the impact of inclusive politicies on parental well-being.